Local and On-the-fly Choreography-based Web Service Composition - Mitra, Saayan; Basu, Samik; Kumar, Ratnesh (Proceedings of the IEEE/WIC/ACM International Conference on Web Intelligence, 2007)
We present a goal-directed, local and on-the-fly algorithm for verifying the existence and synthesizing a choreographer forWeb service composition. We use i/o-automata to represent services, the desired functionality of the composition, and a choreographer to achieve the desired service by composing the existing ones. Choreographer existence and synthesis are typically performed by identifying all possible compositions realizable from the existing services and verifying whether one such composition conforms to the desired required functionality. Such a technique is subject to state-space explosion. In light of this, we have developed a tabled-logic programming technique which generates and explores compositions in a goal-directed fashion to prove/disprove the existence of choreographer and to infer whether the desired functionality is realizable. We present a prototype implementation and show the practical applicability of our technique using a variety of composition problems with the corresponding computational savings in terms of number of states and transitions explored.